Representativeness of protected woody plant taxa in the Ukrainian Carpathians: a descriptive assessment based on inventory data - Popovych, Serhii; Tertyshnyi, Anatolii (Ecological Questions, 2026)
The problem of biodiversity conservation is effectively solved by the mechanism of forming a geographically complete network of protected areas. Network optimization is based on the results of an analysis of its biodiversity representativeness. This area of research is relevant because the results of the analysis encourage the search and creation of new nature reserves. The aim of the study was to analyse the current state of representativeness of rare taxa of woody plants of the Ukrainian Carpathian nature reserve fund. The results of the analysis for this category of plants were conducted for the first time. It is based on the methodology of a systematic approach and differentiated assessment of the state of representativeness of the taxonomic composition. The basic principle of determining the degree of representativeness is quantitative. The greater the number of occurrences, the higher the degree of representativeness of taxa. The composition of taxa was obtained based on the results of their inventory. Fractions of the composition of taxa were distinguished by the criterion of their origin - natural, introduced. The first fraction is represented by Pinus cembra L., Torminalis glaberrima (Gand.) Sennikov & Kurtto (synonym: Sorbus torminalis (L.) Crantz), Taxus baccata L., which are most widely distributed in the nature reserve fund of the Ukrainian Carpathians. The highest indicators of the number of taxa of this fraction are characteristic of the central part of the Ukrainian Carpathians. The most representative species of the introduced and taxonomically richest fraction were Thuja occidentalis L., Larix decidua Mill. and Picea pungens Engelm. Larix decidua has the highest degree of representativeness in the categories of the nature reserve fund. The largest number of introduced taxa is concentrated in botanical gardens. The greatest concern is caused by taxa that are not found in the nature reserve fund (30 species). Or occur in one reserve locality. Therefore, identifying locations and creating new nature reserve territories is primarily necessary for these taxa. They have zero and the lowest levels of representativeness. These are mostly vulnerable, threatened, and endangered taxa.